Age-related decline in melatonin contributes to enhanced osteoclastogenesis via disruption of redox homeostasis - Di-Zheng Wu; Guo-Zheng Zhu; Kai Zhao; Jia-Wen Gao; Gui-Xing Cai; Hong-Zhou Li; Yu-Sheng Huang; Chen Tu; Jing-Shen Zhuang; Zhi-Wei Huang; Zhao-Ming Zhong (BMC, 2024)
Abstract Background Increased oxidative stress contributes to enhanced osteoclastogenesis and age-related bone loss. Melatonin (MT) is an endogenous antioxidant and declines with aging. However, it was unclear whether the decline of MT was involved in the enhanced osteoclastogenesis during the aging process. Methods The plasma level of MT, oxidative stress status, bone mass, the number of bone marrow-derived monocytes (BMMs) and its osteoclastogenesis were analyzed in young (3-month old) and old (18-month old) mice (n = 6 per group). In vitro, BMMs isolated from aged mice were treated with or without MT, followed by detecting the change of osteoclastogenesis and intracellular reactive oxygen species (ROS) level. Furthermore, old mice were treated with MT for 2 months to investigate the therapeutic effect. Results The plasma level of MT was markedly lower in aged mice compared with young mice. Age-related decline in MT was accompanied by enhanced oxidative stress, osteoclastogenic potential and bone loss. MT intervention significantly suppressed the receptor activator of nuclear factor-κB ligand (RANKL)-induced osteoclastogenesis, decreased intracellular ROS and enhanced antioxidant capacity of BMMs from aged mice. MT supplementation significantly attenuated oxidative stress, osteoclastogenesis, bone loss and deterioration of bone microstructure in aged mice. Conclusions These results suggest that age-related decline of MT enhanced osteoclastogenesis via disruption of redox homeostasis. MT may serve as a key regulator in osteoclastogenesis and bone homeostasis, thereby highlighting its potential as a preventive agent for age-related bone loss.